PTPN22 gene polymorphism in Behcet's disease - DİRESKENELİ, RAFİ HANER (WILEY, 2007)
A functional single nucleotide polymorphism (SNP) of PTPN22 gene encoding the protein tyrosine phosphatase has been reported to be associated with autoimmune disorders such as rheumatoid arthritis, systemic lupus erythematosus and type I diabetes. PTPN22 R620W polymorphism has a wide variation of allelic frequencies among different populations. This polymorphism is investigated in Turkish patients with Behcet's disease (BD), a systemic vasculitis with immune activation. DNA samples from 134 patients with BD and 177 healthy controls are genotyped by polymerase chain reaction (PCR)-restriction fragment length polymorphism method for the SNP (rs2476601, A/G) of PTPN22 gene. Polymorphic region was amplified by PCR and digested with XcmI enzyme. The frequency of heterozygous genotype (AG) was 5.1% (9/177) in control group, whereas polymorphic allele was not present in the whole BD group (P = 0.012, OR 0.65, 95% confidence interval 0.0-1.1). Both the lower prevalence in the general population and the absence in BD show the limited role of PTPN22 polymorphism in the pathogenesis of autoimmunity in Turkey.
Keywords: Behcet's disease; PTPN22; single nucleotide; polymorphism; LYMPHOID TYROSINE PHOSPHATASE; AUTOIMMUNE-DISEASES; ASSOCIATION; LOCUS